Passively Q-switched Erbium-doped fiber laser with Tris (8-hydroxyquinolinato) aluminium (Alq3) film saturable absorber - Md Johari, Md Ashadi; Mohamad Samsamnun, Farina Saffa; Mohd. Sarjidan, Mohd Arif; Zulkipli, Nur Farhanah; Ishak, Zurida; Muslim, Norliana; Rosol, Ahmad Haziq Aiman; Aminuddin Jafry, Afiq Arif; Md Sallah, Siti Sarah; Wadi Harun, Sulaiman; Apsari, Retna (Semarak Ilmu Publishing, 2025)
This paper experimentally demonstrates Q-switched Erbium-doped fiber laser (EDFL) by using organic semiconductor material Tris (8-hydroxyquinolinato) aluminium (Alq3) in the form of thin film as a saturable absorber (SA). The fabricated Alq3 thin film is cut into small pieces and incorporated between two ferrules in EDFL cavity, a stable and compact Q-switching pulse train was achieved. As the 980 nm pump power was increased from 45 mW to 98 mW, the repetition rate of the EDFL increased from 70.42 kHz to 91.24 kHz while the pulse width became narrower from 4.48 µs to 3.26 μs. The maximum pulse energy and peak power is 73.214 nJ and 22.458 mW is generated with repetition rate and pulse width of 70.42 kHz and 3.26 μs, respectively. The findings suggest that the proposed Alq3 material is viable as a saturable absorber (SA) in achieving a consistently stable and adaptable Q-switched laser for operation at 1.5 μm wavelength.